Delayed onset panuveitis following intravitreal aflibercept injection. (11th June 2014) - Glading, Jodi A; Lake, Stewart R; Craig, Jamie E; Supramaniam, Devaraj
Abstract : Aflibercept has been listed on the Australian Pharmaceutical Benefit Scheme for the past year for neovascular age-related macular degeneration. Since that time there have not been any reports of delayed onset panuveitis. We present two cases of anterior and posterior uveitis that have occurred 4 weeks or more after first intravitreal injection of aflibercept. Both patients had received other vascular endothelial growth factor inhibitors prior to aflibercept administration without signs of inflammation and both cases had sterile endophthalmitis. On resolution of the inflammation the patients were recommenced on ranibizumab without further incident.